Mapping and evaluationof the changes in the land uses of selected river in the basing northern province - A research based on geographical information system - Subajini, U. (University of Jaffna, 2017)
Researches on the land use patterns of an area are indispensable to the evaluation of the land development activities therein. Though such studies of land use patterns are made in variuos ways, the standards of such evaluation vary depending on the levels of such studies. The changes in land use refer to the identification of various differences found on the surface of the earth in the area concerned, at least within two distinct periods. Following the rehabilition activities in the areas affected by the internal war in the Northern Province, rapid development activities have led to changes in the land use patterns too. As a result, mapping and evaluation of the changes that occurred in a large scale within a short period have become necessary. in this regard the purpose of this research is to map and evaluate the land use changes that have taken place within the three selected river basins in the north of Sri Lanka viz: The river basins of Kanagarayanaru, peraru and paliaru. The changes in land use have been studied and evaluated with the help of GIS technology, using data obtained from such sources including participatory field work, satellite images (Geo-Eye-2016,0.5 meter spatial resolution) and digital land use maps of the survey department. Through these the changes that occurred within two years (2010, 2016) have been evaluated. Though the changes in the land use patterns within the research area appear tangible, during future planning activities, it is important that due to consideration is given to the availability of suitable land, their uses, the needs of the people in such areas, their likes as well as their opinions. As such, This research, while having mapped the land uses and the changes therein, one is able to note these changes quantitatively and qualitatively. It is also expected that this study should be guidance to future researches undertaken on the river basins on North Sri Lanka as well as on other river basins elsewhere in Sri Lanka.
Keywords: River basin; Land use; Land use change; Mapping; Evaluation